IT Evaluasi Layanan Teknologi Informasi Menggunakan Kerangka Kerja ITIL V.3: Evaluasi Layanan Teknologi Informasi Menggunakan Kerangka Kerja ITIL V.3 - muhammad anis (JUPIK : Jurnal Penelitian Ilmu komputer, 2025)
This study evaluates the Information Technology (IT) services at PT Triputra Sejahtera using the ITIL v3 framework in the Service Operation domain, specifically Service Desk and Incident Management. The background of the research is the high ticket load (±500 tickets/month in 2017 and an upward trend from 2013 to 2016 from ~4,000 to ~6,000 tickets/year) and the absence of formal ITSM standards—operations still rely on internal SOPs for “Problem Monitoring.” This caused operational disruptions and necessitated improvements in service governance. The research objective was to measure the level of maturity and compliance with ITIL v3 and formulate recommendations for improvement. The methodology uses the TIPA approach (definition, preparation, assessment, analysis stages), with data collection through observation, the ITIL Service Support Self-Assessment questionnaire and the ITIL Maturity Model (Rudd & Sansbury, 2013), as well as interviews; data processing follows the ITIL v3 guidelines. The results show that the Service Desk passed Levels 1–3.5 but failed at Level 4 (Management Information) and Level 5 (User Interface); overall maturity stopped at Level 3.5 with a Standard Comply status. Incident Management also passed Levels 1–3.5; Level 4 failed, Level 4.5 (External Integration) achieved 3M+3, but Level 5 (Customer/User Interface) was not met (score 0); aggregate maturity stopped at Level 3.5 with Standard Comply. Key recommendations include: strengthening service performance information management (reporting/monitoring), implementing systematic user satisfaction measurement, refining SLA/OLA/UC, improving the known error database and escalation workflow, and integrating cross-functional processes in accordance with ITIL v3 practices. Keywords: ITIL v3, Service Operation, Service Desk, Incident Management, TIPA, maturity, compliance.